Synthesis and structural insights of bis(2-methoxy-6-{[(2-methylpropyl)imino]methyl}phenolato) nickel (II) complex through DFT and docking investigations - K. Jayachandiran; Sv. Esha; M. Savitha Lakshmi; S. Mahalakshmi; S. Arockiasamy (Scientific Reports)
Abstract Nickel complexes are a potential candidate for antibacterial and antifungal activity. A new Ni (II) complex, bis(2-methoxy-6-{[(2-methylpropyl)imino]methyl}phenolato)nickel (II) (2), was synthesised by reacting, bis(3-methoxy-salicylaldehyde)nickel (II) (1) with isobutylamine. It was characterised by single crystal X-ray diffraction (ScXRD), UV-Vis, NMR, IR, mass spectrometry, and thermogravimetry (TG) to study its structure and physico-chemical properties. The ScXRD showed a square planar geometry, and monoclinic crystal system with a space group P21/n. The TG analysis revealed its thermal durability pre and post-melting up to 225 oC with a weight loss of only 2%. The optimized molecular structure, energy gap between HOMO and LUMO, and intermolecular interactions were studied by computational methods. The microbial activity evaluation showed significant anti-bacterial activity against E. coli and S. aureus when the concentration exceeded 40 µg/mL, and a prominent anti-fungal activity over C. albicans and C. tropicalis above 30 µg/mL. The values of minimum inhibitory concentration (MIC) for bacteria (MIB) and fungi (MIF) implied its potential to inhibit the growth of microbes. Docking studies revealed that the molecule binds well with proteins such as PDB: 2W9H for Dihydrofolate Reductase of S.aureus as shown by its binding energy of -8.62 kcal.mol− 1.